DEVELOPMENT OF NANOTECHNOLOGIES IN THE CONTEXT OF GLOBAL MARKET TRENDS: PROSPECTS OF INDUSTRY 5.0 - KRAVCHYK, Yuriy (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the study, attention is updated to the issues of innovative and technological development of the national economy, in particular in the aspect of the development of nanotechnology as a factor in the development and scaling of industry 5.0 and strengthening the technological competitiveness of the national economy. Based on these principles, the purpose of the article is to identify the means of nanotechnology development in the context of global market trends and prospects for the progress of Industry 5.0. It is shown that the development of nanotechnology serves as a powerful factor in the technological modernization of the national economy system and concerns the use and manipulation of processes and materials of objects on a nanometer scale. It is argued that the scaling of Industry 5.0 is a new stage in the development of smart manufacturing and a new phase of neo-industrialization, shifting the emphasis from aspects of digital technologies to factors of sustainable development.The development of nanotechnology is closely correlated with another modern trend – the emergence and spread of Industry 5.0. It is a new stage in the development of smart manufacturing and a new phase of neo-industrialization, where the focus shifts from the aspects of digital technologies to the factors of sustainable development, circular production and strategic governance. In fact, it is about the introduction of a joint working environment of man and robot, as well as the creation of a smart society. Industry 5.0 is closely related not only to human-robot cooperation, the creation of robotic factories, but also focuses on the sustainable development of territories, the development of the green and blue economy, the preservation of the natural environment, and social responsibility. This reorientation is based on the notion that technology can be adapted to promote values, and that technological innovation can be based on ethical goals rather than the other way around.It has been proven that the development of nanotechnologies in the Industry 5.0 distribution system requires the formation of a systemic and comprehensive state policy, which is implemented along two vectors: (1) economic; (2) administrative. It is shown that the implementation of state policy in the field of nanotechnology development in the context of global market trends and following the scaling policy of Industry 5.0 requires the implementation of institutional, economic, organizational and informational mechanisms. The leading tools necessary for the development of nanotechnology in Ukraine and the scaling of Industry 5.0 have been identified.
Keywords: nanotechnology; industry 5.0; innovative development; global market; modern trends; economic globalization